2014
DOI: 10.5152/eajm.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Management of Tracheobronchial Injuries

Abstract: Tracheobronchial injury is one of cases which are relatively uncommon, but must be suspected to make the diagnosis and managed immediately. In such a case, primary initial goals are to stabilize the airway and localize the injury and then determine its extend. These can be possible mostly with flexible bronchoscopy conducted by a surgeon who can repair the injury. Most of the penetrating injuries occur in the cervical region. On the other hand, most of the blunt injuries occur in the distal trachea and right m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 23 publications
0
59
0
2
Order By: Relevance
“…Some patients cannot be approached conservatively therefore the most appropriate treatment is the surgical treatment as early as possible. The principles of surgery dictate the following: debridement of devitalized tissue including cartilage, end to end anastomosis, flexion of the neck to avoid anastomosis line tension and supporting the suture line with the local tissues as a flap (7). Left thoracotomy provides a good exposure to the distal left main-stem bronchus, distal part of aortic arch, descending thoracic aorta and proximal left subclavian artery.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients cannot be approached conservatively therefore the most appropriate treatment is the surgical treatment as early as possible. The principles of surgery dictate the following: debridement of devitalized tissue including cartilage, end to end anastomosis, flexion of the neck to avoid anastomosis line tension and supporting the suture line with the local tissues as a flap (7). Left thoracotomy provides a good exposure to the distal left main-stem bronchus, distal part of aortic arch, descending thoracic aorta and proximal left subclavian artery.…”
Section: Discussion:-mentioning
confidence: 99%
“…While median sternotomy ensures optimal access to the hearth and major vessels, it is less beneficial for trachea, carina and bronchi. Moreover, it does not provide appropriate exposure for the restoration of additional esophageal injuries (7). The severity of associated lung injury is taken into consideration regarding the approach and that what exactly what we had to experience.…”
Section: Discussion:-mentioning
confidence: 99%
“…Moreover, thorax CT maintains its effectiveness in inspecting trauma and it is availability in detecting the appearance of possible great vessel injuries, hemopericardium or mediastinal hematoma (12). It may show pneumoderm, pneumomediastinum, pneumothorax, pulmonary atelectasis, respiratory tree deviation or specific site of the separation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common mechanisms are intubation by inexperienced clinicians, dilatative percutaneous tracheotomy, and change of the position of the intubation tube without deflation or overinflation of the tube cuff [2,4] . Relative overinflation of the tube cuff occurs if the tracheal tube is inflated just above the carina and moved back to the narrower upper portion of the trachea.…”
Section: Mechanisms Of Injurymentioning
confidence: 99%
“…Prokakis et al [1] reported that prevalence of ITR in elective orotracheal intubations was 1/20,000-75,000 patients and increased to 15% in emergently performed procedures, and for percutaneous dilatative tracheotomies the estimated incidence is 0.2-0.7%. In the last decade, the estimated incidence of ITR after endotracheal intubation is 0.05-0.37% [1] , with a higher incidence of approximately 0.5-1% reported in cases of double-lumen intubation [2] . The presence of other concomitant pathologies of patients undergoing surgical procedure for this, or those who are treated in intensive care units for other reasons, could lead to an early adverse outcome, ventilator failure, airway obstruction, or death from tension pneumothorax, or late development of airway stenosis and recurrent pulmonary infections [1] .…”
Section: Introductionmentioning
confidence: 99%